A versatile hard-soft N/S-ligand for metal coordination and cluster formation - Benson, Callum; Plajer, Alex; García-Rodríguez, Raúl; Bond, Andrew D.; Singh, Sanjay; Gade, Lutz H.; Wright, Dominic S. (Chemical communications, 2016)
Deprotonation of the thialdiphosphazane [SPH(μ-NtBu)]2 with a range of metal-bases gives the stable dianion [S-P(μ-NtBu)]22−, which is valence-isoelectronic with the widely-used [RN-P(μ-NR)]22− ligand. Structural studies show that the new ligand has adaptable hard-soft character with respect to the coordinated metal centre and that its multidentate nature can be exploited to construct large cage architectures.
Gesehen am 06.05.2020